Molecular Determinants in tRNA D-arm Required for Inhibition of HIV-1 Gag Membrane Binding - Sumner, Christopher; Kotani, Osamu; Liu, Shuohui; Musier-Forsyth, Karin; Sato, Hironori; Ono, Akira (Journal of molecular biology, 2022)
[Display omitted] •Features of tRNA contributing to inhibition of HIV-1 Gag membrane binding are unclear.•Membrane binding of purified MA is strongly inhibited by tRNALys3 but not tRNAPro.•The D arm but not anticodon arm contributes to strong inhibition by tRNALys3.•The D arm sequence and its context are major determinants for the inhibitory effect. Plasma-membrane-specific localization of Gag, an essential step in HIV-1 particle assembly, is regulated by the interaction of the Gag MA domain with PI(4,5)P2 and tRNA-mediated inhibition of non-specific or premature membrane binding. Different tRNAs inhibit PI(4,5)P2-independent membrane binding to varying degrees in vitro; however, the structural determinants for this difference remain unknown. Here we demonstrate that membrane binding of full-length Gag synthesized in vitro using reticulocyte lysates is inhibited when RNAs that contain the anticodon arm of tRNAPro, but not that of tRNALys3, are added exogenously. In contrast, in the context of a liposome binding assay in which the effects of tRNAs on purified MA were tested, full-length tRNALys3 showed greater inhibition of MA membrane binding than full-length tRNAPro. While transplantation of the D loop sequence of tRNALys3 into tRNAPro resulted in a modest increase in the inhibitory effect relative to WT tRNAPro, replacing the entire D arm sequence with that of tRNALys3 was necessary to confer the full inhibitory effects upon tRNAPro. Together, these results demonstrate that the D arm of tRNALys3 is a major determinant of strong inhibition of MA membrane binding and that this inhibitory effect requires not only the D loop, which was recently reported to contact the MA highly basic region, but the loop sequence in the context of the D arm structure.